2016
DOI: 10.1016/j.cellsig.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Shoc2-tranduced ERK1/2 motility signals — Novel insights from functional genomics

Abstract: The extracellular signal-regulated kinase 1 and 2 (ERK1/2) pathway plays a central role in defining various cellular fates. Scaffold proteins modulating ERK1/2 activity control growth factor signals transduced by the pathway. Here, we analyzed signals transduced by Shoc2, a critical positive modulator of ERK1/2 activity. We found that loss of Shoc2 results in impaired cell motility and delays cell attachment. As ERKs control cellular fates by stimulating transcriptional response, we hypothesized that the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…In this previous study, SHOC2 could alter signaling connections and re-route oncogenic Ras signals to Raf-1 in order to mediate reactivation of the ERK1/2 pathway and facilitate drug resistance in cells (14). SHoc2 has also been shown to be a positive regulator that contributes to the malignant properties of different tumor cells by modulating the growth, transformation, migration and invasion of cancer cells (10,15,16). Our preliminary experiments revealed that SHOC2 was highly expressed in McF-7 and Mda-MB-231 breast cancer cells (data not shown).…”
Section: Introductionmentioning
confidence: 95%
“…In this previous study, SHOC2 could alter signaling connections and re-route oncogenic Ras signals to Raf-1 in order to mediate reactivation of the ERK1/2 pathway and facilitate drug resistance in cells (14). SHoc2 has also been shown to be a positive regulator that contributes to the malignant properties of different tumor cells by modulating the growth, transformation, migration and invasion of cancer cells (10,15,16). Our preliminary experiments revealed that SHOC2 was highly expressed in McF-7 and Mda-MB-231 breast cancer cells (data not shown).…”
Section: Introductionmentioning
confidence: 95%
“…In contrast to the canonical Ras proteins, constitutively active M-Ras has a low transforming activity and is rarely mutated in human cancer (Quilliam et al, 1999); however, gain-of-function mutations in M-RAS have been iden-tified in patients with Noonan syndrome (Higgins et al, 2017). Notably, mutations in one of the distinct effectors of M-RAS, the SHOC2 scaffold, have also been detected in Noonan patients (Cordeddu and Di, 2009;Hannig et al, 2014), and, likewise, Shoc2 has been implicated in cell migratory events (Young et al, 2013;Kaduwal et al, 2015;Jeoung et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…SHOC2 is an evolutionarily conserved protein, composed of an unstructured N-terminal domain and a long stretch of leucine-rich repeats (LRRS) (Jeoung et al, 2013). The N-terminal domain binds to RAS and RAF to activate ERK1 and ERK2 (Dai et al, 2006; Jeoung et al, 2013; Jeoung et al, 2016). In addition, SHOC2 is upregulated in the majority of human cancers (Young et al, 2013).…”
Section: Introductionmentioning
confidence: 99%